Peranan Orangtua Dalam Mengantisipasi Dekadensi Akhlak Pada Anak Remaja - Nurcahyani Nurcahyani; Siti Aminah; Agus Suryana (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
This research was motivated by the large number of students experiencing low morals. With this background, researchers are interested in examining whether there is an influence on the role of parents to overcome moral decline. The research was conducted at SMA Taman Islam, Cibungbulang District, Bogor Regency. The study population was 126 students while the sample was 30 students with a purposive sampling technique. This study applies the correlation method with the research instrument using a questionnaire for the family environment and the value of report cards for learning outcomes of Islamic education. Data were analyzed using the product moment correlation technique. The results of the study at the menu level of significance with the t test showed t count 1.84960> t table 1.70113, this means that the influence of parental roles on student morals is shown by KD (coefficient of determination) = 0.1089% which means that the family environment contributes to a contribution of 10, 89% of students' PAI learning outcomes.